Effect of ionic interactions on crystallization of star telechelic poly (L-lactide) ionomers - Kulkarni, Amruta (Polymer, 2022)
Effect of ionic interactions on crystallization properties of star telechelic poly(L-lactide) ionomers was studied by performing isothermal crystallization experiments. We report a comparison between star PLLA and star telechelic PLLA ionomer. It was evident that the ionic interactions in the ionomer affected the crystallization rate as well as modified the spherulitic morphology. Employing Avrami analysis on the isothermal crystallization data we show that star PLLA shows faster crystallization at higher temperatures (closer to melting point) than the star PLLA ionomer. However, a reversal of this trend in crystallization is observed at lower temperatures (closer to glass transition temperature). The origin of high temperatures behaviour comparison is explained in terms of the higher secondary nucleation barrier for ionomers using the famous Lauritzen- Hoffman secondary nucleation theory. However, we point out that the assumption of equal diffusion barrier in this theory limits its range of applicability. In order to explain the low temperature behaviour, we invoke the activation energy comparison in PLLA and ionomer using rheological studies. We show that although the presence of ions in the polymer impede the secondary nucleation process, its effect is only observed at higher temperatures.
Keywords: Crystallization; Ionomer; Poly( L -lactide); Star polymer; Telechelic